Relevansi Informasi Laporan Keuangan Accrual Basis: Kemampuan Rasio Keuangan Dalam Memprediksi Status Financial Distress Pemerintah Daerah Kabupaten Dan Kota Se- Indonesia Periode 2015-2017 - Waninda Waninda; Fefri Indra Arza (Jurnal Eksplorasi Akuntansi, 2019)
This study aims to predict the financial distress status of district and city governments in Indonesia. Research examines the relevance of financial statement information consisting of profitability ratio, liquidity ratio, performance ratio and capital stress ratio in predicting district and city government financial distress in Indonesia in 2015-2017. This study uses agency theory. The sampling method in this study used purposive sampling. This study consisted of 134 samples of districts / cities in Indonesia, the financial data used in the study were audited regional government financial reports, namely reports on audit results for 2015-2017. The type of data used is secondary data. The analysis used is binary logistic regression analysis. Based on the results of binary logistic regression analysis with a significance level of 5%, that of the four types of ratios measured using fourteen measurements obtained results (1) Profitability ratio as measured by profit margin ratio affects financial distress with an β coefficient of 51,548 and a significance value of 0,000 < 0.05, (2) The performance ratio measured by operating revenue to total revenue has an effect on financial distress with an β coefficient of -41.180 and a significance value of 0.015> 0.05, and a depreciation ratio influences financial distress with an β coefficient of 40.004 and a value significance of 0.004 <0.05